1986
DOI: 10.1079/bjn19860127
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplementation with maize starch and level of intake of perennial ryegrass (Lolium perenne cv. Endura) hay on the removal of digesta from the rumen of sheep

Abstract: 1. Eight wether sheep were offered a diet of perennial ryeigrass (Loliumperenne cv. Endura) hay once daily at two levels of intake (1 1 and 16.5 g dry matter (DM)/kg live weight (LW)) with or without maize starch (175 g DM/kg hay DM). The experiment consisted of four periods. each lasting 32 d. Rates of digestion of the hay were measured by incubation in dacron bags and rates of passagc using chromium-mordanted hay. Rumen pool sizes of DM, organic matter and fibre were measured by emptying the rumen.2. The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…On the other hand, the intrinsic activity of microbes, which depends mainly on ruminal milieu, is not largely modified by intake (Doreau et al, 2003). This is shown by the low variation in situ OM and fibre degradation of some forage (Aitchison et al, 1986). Contrary, protein degradability seems to increase when intake decreases, as revealed by direct measurements of non-microbial protein duodenal flows in sheep (Merchen et al, 1986) or by in situ ruminal measurements in goats (Zhao et al, 1993).…”
Section: Intake Of Nutrientsmentioning
confidence: 66%
See 2 more Smart Citations
“…On the other hand, the intrinsic activity of microbes, which depends mainly on ruminal milieu, is not largely modified by intake (Doreau et al, 2003). This is shown by the low variation in situ OM and fibre degradation of some forage (Aitchison et al, 1986). Contrary, protein degradability seems to increase when intake decreases, as revealed by direct measurements of non-microbial protein duodenal flows in sheep (Merchen et al, 1986) or by in situ ruminal measurements in goats (Zhao et al, 1993).…”
Section: Intake Of Nutrientsmentioning
confidence: 66%
“…Organic matter digestibility decreased with underfeeding (64.5 and 53.7%, respectively, at high and low intakes) without modification of mean ruminal or total tract retention times (Grimaud et al, 1999) and they also confirm that, at intakes below maintenance, digestibility can decrease when feed intake is restricted, contrary to the general view described in the literature. Conversely, with forage based diets in situ DM degradability either did not vary (Aitchison et al, 1986) or increase (Kabre et al, 1995) when intake decreased and digestibility increased. Kabre et al (1994) found that such an increase was due to a higher enzymatic activity of cellulolytic bacteria.…”
Section: Body Weight Changes Digestibility Of Nutrients and Plane Ofmentioning
confidence: 81%
See 1 more Smart Citation
“…Most investigators have found that MRT of particles and of fluid decreases when level of feed intake increases (Thornton and Minson 1972;Grovum and Williams 1977;Mudgal et al 1982;White et al 1984;Ledoux et al 1985;Aitchison et al 1986;Faichney and Gherardi 1986;Merchen et al 1986;Shaver et al 1986;Waghorn et al 1986;Funk et al 1987;Deswysen and Ellis 1988;Lindberg 1988;Uden, 1988). However, doubling the intake leads to only a 20-40% decrease of particle MRT in the forestomach; and some investigators have not found any significant effect of the intake level on MRT (Ulyatt et al 1984;Van Vuuren 1984).…”
Section: β Influence Of Feed Intakementioning
confidence: 99%
“…23 The rate constants for passage from the rumen were estimated for hay by fitting the model of Dhanoa et al 24 to the excretion patterns of chromium-mordanted hay, as described by Aitchison et a1.21. 22 These estimates were termed kh and kl, respectively.…”
Section: Extent Of Digestion [G (G Ndf Intake)-']mentioning
confidence: 99%